Interdependensi Aspek Sdm Berbasis Stres Kerja Dalam Upaya Capaian Kinerja Pegawai - Nurul Puspitaningrum; Adya Hermawati; Muklish H Mas’ud (EKONOMI & SOSIAL, 2021)
This writing analyzes the effect of workload and competence on employee performance, either directly or indirectly through the mediation of work stress. Quantitative method using the SEM-PLS program. Data was collected by means of a questionnaire which was distributed to 90 actors in the procurement of goods/services in Pasuruan Regency. Empirical evidence obtained is that workload has a positive and significant effect on employee performance, competence has a positive and significant effect on employee performance, work stress has a positive and significant effect on employee performance, workload has a positive and significant effect on employee performance directly, but is not mediated by work stress, competence has a positive and significant effect on employee performance directly, but is not mediated by work stress. So even though there are demands for the needs of the environment, the organization and the individual employees concerned, as well as demands for mastery of knowledge, skills and work attitudes, these things cannot increase/decrease the results of performance achievements, benefits and employee behavior or not achieve work targets. This is because the actors in the procurement of goods/services are able to turn it into eustress, which is the result of a healthy, positive, and constructive (constructive) response to stress.